Modelling of Prognosis for Bioenergy Production in Ukraine - Hryhoruk, Iryna; Yakubiv, Valentyna; Sydoryk, Yurii; Maksymiv, Yuliia; Popadynets, Nazariy (International Journal of Energy Economics and Policy, 2021)
Promoting renewables, in particular bioenergy, is vital to move Ukraine towards a low-carbon economy. Decision-makers might turn to bioenergy projections for developing their policies or investments. This paper presents statistical calculations and economic-mathematical modeling of the state of the bioenergy sector in Ukraine. Using Spearman’s rank correlation coefficient, correlations between different factors influencing biofuel production were investigated. Modeling of the forecast of biofuel production was done with the use of a multiple regression equation, which provides for the creation of a standard linear model. It enables predicting future development of renewable energy and bioenergy, highlighting and choosing the most appropriate factors to be stimulated by the government in order to achieve the goals of renewable energy development and energy security as a result. Keywords: Bioenergy, Renewables, Energy Security, Energy Strategy JEL Classifications: Q42, Q38, O13, P28 DOI: https://doi.org/10.32479/ijeep.11741